Audit committee characteristics and voluntary disclosure: evidence from Malaysian listed firms / Hisham Kamel Madi, Zuaini Ishak and Nor Aziah Abdul Manaf - Madi, Hisham Kamel; Ishak, Zuaini; Abdul Manaf, Nor Aziah (2013)
Global economic crisis in 2008 has increased the focus on the role of audit committee in ensuring integrity and transparency in corporate reporting. Audit committee characteristics are crucial in determining the ability of audit committee in carrying out its responsibilities effectively. Hence, this study aims to investigate the contribution of audit committee characteristics; independence, accounting expertise, multiple directorship, size, and diligence to audit committee effectiveness over corporate voluntary disclosure by Malaysian listed firms. The study uses 146 firms listed on Bursa Malaysia for the year 2006. The empirical results have revealed that proportion of independent directors, and number of directors on audit committee is significantly associated with corporate voluntary disclosure, and hence enhances audit committee effectiveness. The study contributes to the understanding of the association between audit committee characteristics and such committee effectiveness in respect to voluntary disclosure practices.